The Application of Platelet-Rich Plasma for Patients Following Total Joint Replacement: A Meta-Analysis of Randomized Controlled Trials and Systematic Review - Shu, Hongxin; Huang, Zhenjun; Bai, Xinyan; Xia, Zhiyu; Wang, Nanye; Fu, Xiaoling; Cheng, Xigao; Zhou, Bin (Frontiers in Surgery, 2022)
Background: The clinical efficacy of platelet-rich plasma (PRP) in the treatment of total joint replacement (TJR) remains inconclusive. In this paper, systematic review and meta-analysis were adopted to assess the efficacy of using PRP for the treatment of TJR. Methods: A comprehensive search of Medline, Embase, and Cochrane library databases for randomized controlled trials (RCTs) articles recording data of PRP for TJR was conducted from inception to February 2022. Outcomes concerned were pain, range of motion (ROM), WOMAC score, length of hospital stay (LOS), hemoglobin (Hb) drop, total blood loss, wound healing rate and wound infection. The methodological quality of the included RCTs was evaluated by using the Cochrane Risk of Bias Tool 2.0 (RoB 2.0). The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) was utilized to assess the level of evidence for the outcomes. Subgroup analysis was conducted according to the type of TJR. Results: Ten RCTs were included in the meta-analysis. In the TKA subgroup, the available data demonstrated that there were significant differences in the outcomes of pain and Hb drop, while it was the opposite of ROM, WOMAC score, LOS, total blood loss, wound healing rate, and wound infection. In the THA subgroup, no significant differences can be seen between two groups in the outcomes of LOS and wound infection. However, PRP group gained a higher wound healing rate in the THA subgroup. Conclusion: The application of PRP did not reduce blood loss, but improved the wound healing rate. However, more prospective and multicenter studies are warranted to confirm these results.